2012
DOI: 10.1002/eco.1275
|View full text |Cite
|
Sign up to set email alerts
|

Multiple drift responses of benthic invertebrates to interacting hydropeaking and thermopeaking waves

Abstract: Sudden instream releases of hypolimnetic water from hydropower plants [i.e. hydropeaking (HP)] can cause abrupt temperature variations [i.e. thermopeaking (TP)], typically on a daily basis. The propagation of discharge and thermal waves is asynchronous, causing the benthic community to undergo two different but consecutive impacts. Invertebrates respond to sudden increases in discharge with catastrophic drift, and respond to sudden changes of temperature with behavioural drift. Owing to the time lag separating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
104
1
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(112 citation statements)
references
References 99 publications
5
104
1
2
Order By: Relevance
“…In the dry season, with fluctuating flows there were no differences in density between sampling times, but richness was higher in night samples. Invertebrates responded to the fluctuating flow periods with catastrophic drift, probably as a consequence of the sudden increase in bottom shear stress (Bruno et al, 2012). The difference in drift richness is a consequence of the sensitivity of each taxon to flow fluctuations, related to the degree of adaptation to resist increased current velocities or to move toward refuge habitats (Ce´re´ghino et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In the dry season, with fluctuating flows there were no differences in density between sampling times, but richness was higher in night samples. Invertebrates responded to the fluctuating flow periods with catastrophic drift, probably as a consequence of the sudden increase in bottom shear stress (Bruno et al, 2012). The difference in drift richness is a consequence of the sensitivity of each taxon to flow fluctuations, related to the degree of adaptation to resist increased current velocities or to move toward refuge habitats (Ce´re´ghino et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Today, experimental flumes of different typology have become a common tool to study the responses of biological communities to physical, chemical, hydrological manipulations, using behavioral and catastrophic drift as the measured response and based on the hypothesis that any invertebrate showing an immediate avoidance or displace-N o n -c o m m e r c i a l u s e o n l y ment reaction would rapidly drift (Holomuzki and Biggs, 2000;Imbert and Perry, 2000;Suren and Jowett, 2001;Mochizuki et al, 2006;Carolli et al, 2012;Fenoglio et al, 2013;Bruno et al, 2013Bruno et al, , 2016. Although drift catches in these simulations were often high, it is difficult to assess the significance of these responses, since if a high proportion of the benthos enters the drift for a short period of time, the drifting invertebrates may have originated from the area immediately downstream from the disturbance and could have returned rapidly to the benthos and thus not have been caught.…”
Section: Introductionmentioning
confidence: 99%
“…Céréghino and Lavandier (1998) found that frequent thermal modifications to stream water can lead to changes in macroinvertebrate growth, flight, and emergence patterns. Following hydropeaking, Carolli et al (2012) and Bruno et al (2013) observed in experiments increased macroinvertebrate drift associated with warm and cold thermopeaking. By contrast, results of an experimental study by Schülting et al (2016) suggest that hydropeaking and cold thermopeaking together have an antagonistic effect on drift for aquatic macroinvertebrates.…”
Section: Water Temperaturementioning
confidence: 94%
“…Water temperature changes during a hydropeaking event are referred to as thermopeaking. A thermal wave usually occurs shortly after an increase of discharge (Toffolon et al 2010) and may act as an additional stressor on river biota (Bruno et al 2013). This additional thermal stressor can have severe impacts on the periphyton biomass development and community composition.…”
mentioning
confidence: 99%